A critical narrative inquiry to understand the impacts of an overdose prevention site on the lives of site users - Abe Oudshoorn; Michelle Sangster Bouck; Melissa McCann; Shamiram Zendo; Helene Berman; Jordan Banninga; Marlene J. Le Ber; Zayya Zendo (BMC, 2021)
Abstract Background Globally, communities are struggling to gain support for harm reduction strategies being implemented to address the impacts of substance use. A key part of this discussion is understanding and engaging with people who use drugs to help shape community harm reduction strategies. This study focused on how an overdose prevention site has influenced the lives of people who use drugs. Methods A critical narrative method was utilized, centred on photo-narratives. Twenty-seven individuals accessing an overdose prevention site were recruited to participate in preliminary interviews. Sixteen participants subsequently took photographs to describe the impact of the site and participated in a second round of interviews. Through independent coding and several rounds of team analysis, four themes were proposed to constitute a core narrative encompassing the diverse experiences of participants. Results A key message shared by participants was the sense that their lives have improved since accessing the site. The core narrative proposed is presented in a series of four themes or "chapters": Enduring, Accessing Safety, Connecting and Belonging, and Transforming. The chapters follow a series of transitions, revealing a journey that participants presented through their own eyes: one of moving from utter despair to hope, opportunity, and inclusion. Where at the outset participants were simply trying to survive the challenges of chaotic substance use, through the relationships and services provided at the site they moved towards small or large life transformations. Conclusions This study contributes to an enhanced understanding of how caring relationships with staff at the overdose prevention site impacted site users' sense of self. We propose that caring relationships are an intervention in and of themselves, and that these relationships contribute to transformation that extends far beyond the public health outcomes of disease reduction. The caring relationships at the site can be a starting point for significant social changes. However, the micro-environment that existed within the site needs to extend beyond its walls for true transformative change to take place. The marginalization and stigmatization that people who use drugs experience outside these sites remains a constant barrier to achieving stability in their lives.